Association of common genetic variants with vitamin D status in Malaysian children with epilepsy. (July 2020) - Kong, Ann Nie; Fong, Choong Yi; Ng, Ching Ching; Mohamed, Ahmad Rithauddin; Khoo, Teik Beng; Ng, Rui Lun; Jalaludin, Muhammad Yazid; Nadarajaw, Thiyagar
Highlights: GC-rs4588 polymorphism is associated with lower 25(OH)D concentrations in both Malaysian children with epilepsy and Malaysian healthy children. VDR-rs7975232-A (ApaI) polymorphism is associated with lower risk of vitamin D deficiency in Malaysian children with epilepsy of Malay ethnicity. Genetic factors play a role in the vitamin D status among children with epilepsy. Abstract: Purpose: Children with epilepsy (CWE) are at risk of vitamin D deficiency. Single nucleotide polymorphisms (SNPs) affecting the vitamin D pathway are potentially important risk factors for serum 25-hydroxyvitamin D [25(OH)D] concentration. The aims of our study were to evaluate the association of vitamin d -related SNPs to serum 25(OH)D concentrations in Malaysian CWE. Methods: Cross-sectional study of Malaysian ambulant CWE on antiseizure medication for >1 year. Sixteen SNPs in 8 genes (GC, VDR, CYP2R1, CYP24A1, CYP27B1, CYP27A1, CYP3A4, NADSYN1/DHCR7) were genotyped. Linear and logistic regression models and co-variates adjusted analyses were used. SNPs with significant associations were further analysed in a group of ethnically-matched healthy Malaysian children. Results: 239 CWE were recruited (52.7% Malay, 24.3% Chinese and 23.0% Indian) with mean serum 25(OH)D of 58.8 nmol/L (SD 25.7). Prevalence of vitamin D deficiency (≤37.5 nmol/L) was 23.0%. Minor allele of GC-rs4588-A was associated with lower serum 25(OH)D in the meta-analysis of both CWE (β -8.11, P = 0.002) and Malaysian healthy children (β -5.08, P < 0.001), while VDR-rs7975232-A was significantly associated with reduced odds of vitamin D deficiency in Malay subgroup of CWE (OR: 0.16; 95% CI: 0.06–0.49; P = 0.001) and this association was not found in the healthy children group. Conclusions: Our results suggest that GC-rs4588 is associated with lower serum 25(OH)D concentration in both Malaysian CWE and healthy children, while VDR-rs7975232A is associated with lower risk of vitamin D deficiency in Malaysian CWE of Malay ethnicity. Our findings may assist in the genetic risk stratification of low vitamin D status among CWE.